Pengukuran Centrality Pada Graf Jaringan Serat Optik Palapa Ring Timur II - Herlina Napitupulu; Ema Carnia; Muhammad Deni Johansyah (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
The study of centrality measurement is still a developing topic recently. Centrality measures can also be applied to palapa networks. In this study, it was determined which city in the connected eastern palapa ring optic fiber network II which had the highest centrality compared to other cities. The calculation is done by measuring four types of centralities, namely degree, closeness, betweenness, and eigenvector. Calculations are done using Python software, and its syntax are given in this paper. The four centrality results from each type are compared and as a result, the most important cities in this eastern palapa ring optic fiber network II are obtained.